Spatial Analysis of Factors Affecting the Formation of Smart Rural Tourism (Case Study: Tourism-Oriented Villages in Eastern Kermanshah Province) - Aliakbar Anabestani; Sajjad Barani Aliakbari (برنامه ریزی فضایی)
AbstractObjective: Smart tourism utilizes communication and information technologies to enhance the visitor experience at tourist destinations. Integration of smart tourism concepts is particularly important in rural areas. By leveraging smart technologies, villages can promote their businesses and improve their tourism infrastructure. The aim of this study was to examine and analyze the factors influencing the development of smart tourism in tourism-oriented villages in eastern Kermanshah Province. Method: This study employed a descriptive-analytical research design. Data were collected through a combination of methods, including a documentary review of library resources and scientific journals, as well as field surveys using questionnaires. The information required for the study of smart rural tourism and its indicators was gathered based on the background literature and regional context. Out of a total of 1,191 rural households, a sample of 215 respondents was selected using Cochran’s formula with a 0.065% margin of error. The one-sample t-test was used to measure the level of smart rural tourism according to the type of data, drawing from Pearson correlation tests. To analyze the impacts of the examined factors on smart rural tourism, the CRITIC weighting and COCOSO ranking methods were used based on the type of data. Additionally, factor analysis was conducted to further explore the impacts of the factors on smart rural tourism. For the statistical analyses, JAMOVI software was utilized, while GIS software was employed for spatial analysis. Findings: The results indicated that the concept of smart rural tourism was characterized by a set of indicators related to smart economy, smart governance, smart infrastructure, smart people, smart connectivity, and smart education. The one-sample t-test revealed that among the indicators of smart rural tourism, the indices of smart governance, smart people, smart economy, and smart education were the most important factors in the studied villages. Specifically, the mean scores for smart governance and smart people were 3.95, while the mean scores for smart economy and smart education were 3.90, suggesting these were the most influential components of smart rural tourism in the research context. Keywords: Smart Tourism, Target Tourism-Oriented Villages, Spatial Analysis, Factor Analysis, Kermanshah Province. IntroductionOver the past decades, the tourism industry has undergone significant changes and developments, largely driven by the rapid growth of technology. As a result, tourism has been increasingly influenced by various innovative approaches, including the concept of "smart tourism". The smart tourism approach has emerged as a response to transformations in the global system enabled by technological advancements. This approach aims to improve resource management efficiency, maximize competitiveness, and enhance sustainability of tourism through the utilization of innovative and technology-focused methods. Given the varying characteristics and contexts of different regions, development of appropriate structures and infrastructure is a crucial consideration. In the case of rural areas, it is necessary to shift from traditional structures to smart structures in order to facilitate the implementation of smart tourism initiatives. Compared to urban settings, rural areas often face unique challenges, which necessitate a thorough understanding and assessment of the current status of smart tourism, identification of existing obstacles, and provision of fundamental solutions to overcome them. This study focused on the spatial analysis of the factors influencing the formation of a smart rural tourism approach in the target tourism-oriented villages in the eastern region of Kermanshah Province. Materials and MethodsThis research employed an applied, descriptive-analytical approach. The study investigated the factors influencing the formation of a smart rural tourism in 7 target tourism villages located in the eastern counties of Kermanshah Province (Harsin, Sahneh, Songhar, and Kangavar). According to the 2016 census, these villages had a total population of 3,888 individuals in 1,191 households. To determine the sample size, Cochran’s formula was used with a 0.65 error rate, resulting in a sample of 215 individuals. The sample was allocated proportionally based on the number of households in each village.Allocation of the sample size across the villages was considered with the objective of analyzing the target settlements for tourism in the study area. A minimum of 10 questionnaires were allocated to each village with the remaining questionnaires distributed proportionally based on the number of households in each village. It is worth noting that the target population of this study consisted of villages with a focus on tourism. Some villages, such as Gara Ban, had gained global recognition and were home to a sect called Ahl-e Haqq Atash Beige or Mashayekhi, who had been actively working to build, maintain, and develop the location using the resources and assistance of their followers. To assess the level of smart rural tourism based on the data type, Pearson correlation tests and one-sample t-tests were employed. Furthermore, due to the need to classify the villages in terms of their progress toward smart rural tourism, weighting methods, such as CRITIC and ranking methods like COCOSO, were used, depending on the data type. Additionally, factor analysis was utilized to analyze the impacts of the examined factors on smart rural tourism. For the statistical analyses, JAMOVI software was used, while GIS software was employed for spatial mapping. Research FindingsTo identify the influential factors, 41 variables were entered into the analysis. Principal component analysis using orthogonal rotation and Varimax type was employed to analyze the factors affecting the formation of smart rural tourism in the target villages located in the eastern counties of Kermanshah Province. Based on the eigenvalues, which represented the share of each factor in the total variance of the variables (with higher values indicating more important and influential factors), the variables were classified into 17 factors. These 17 factors collectively explained 62.80% of the total variance of the factors influencing the formation of smart rural tourism in the target villages. According to the CRITIC method, the factors with the highest weights were tourism economy (0.086), awareness and media (0.076), electronic security (0.073), and electronic marketing (0.072), while media networks (0.037) and trust in virtual spaces (0.044) had the lowest weights among the 17 factors of smart rural tourism. The CoCoSo method was used to rank the villages in terms of their progress toward smart rural tourism. Gara Ban Village ranked first with a final score of 2.266 followed by Kunduleh Village (2.070), Charmaleh Alya Village (1.988), Najobran Village (1.987), and Fash Village (1.925). Villages of Barnaj and Varmaghan ranked 6th and 7th, respectively, indicating that these villages were not in a favorable position in terms of smart rural tourism. Discussion of Results & ConclusionRural areas play a vital role in economic development and their contribution cannot be overlooked. Village as one of the pillars of the settlement system holds special importance. This significance is evident through the influence of various economic sectors, with tourism being a prominent one. Tourism is a social phenomenon that contributes to employment generation and poverty reduction. Smart tourism refers to the use of communication and information technologies to enhance the tourist experience at destinations. In smart tourism, technologies, such as the internet, mobile phones, smart systems, and digital mapping, are employed to provide tourists with necessary information and services. The position of smart tourism in villages is crucial and impactful. By utilizing smart technologies, villages can promote their businesses and enhance their tourism infrastructures. Furthermore, smart systems enable villages to attract tourists more efficiently and compete with larger areas like cities. Smart rural tourism is an innovative approach in the tourism industry that aims to improve tourist experience and enhance the productivity of rural areas by leveraging advanced technologies. This type of tourism seeks to use technologies like the Internet of Things (IoT), Augmented Reality (AR), Artificial Intelligence (AI), Geographic Information Systems (GIS), and other modern tools to improve communication between tourists and rural environments, increase informational and recreational activities, preserve the environment, boost the local economy, and create a unique experience for visitors. In summary, smart rural tourism not only focuses on enhancing tourist experience, but also contributes to the sustainable development of rural areas and preservation of their cultures and natures by combining technology with the tourism industry.